2016
DOI: 10.7567/apex.9.111201
|View full text |Cite
|
Sign up to set email alerts
|

Two-color surface-emitting lasers using a semiconductor coupled multilayer cavity

Abstract: Two-color surface-emitting lasers were demonstrated, employing a GaAs/AlGaAs coupled multilayer cavity composed of two cavity layers and three distributed Bragg reflector (DBR) multilayers. InGaAs multiple quantum wells (MQWs) with two different well widths were introduced only in the upper cavity, and sandwiched between p- and n-type DBRs. This current-injection type device exhibited two-color lasing in the near-infrared region under room temperature pulsed conditions. Two-color lasing was achieved when the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…8,9) We also proposed an original THz emitter possessing a GaAs/AlAs-coupled multilayer cavity structure. [10][11][12][13][14][15][16][17] The compact device had two cavities and three distributed Bragg reflectors (DBRs), and had gain layers in the one of the cavities. By contrast, in the other cavity, DFG of the two-color laser produced in the device was performed, where the generated electromagnetic waves then exhibited THz-wave properties.…”
Section: Introductionmentioning
confidence: 99%
“…8,9) We also proposed an original THz emitter possessing a GaAs/AlAs-coupled multilayer cavity structure. [10][11][12][13][14][15][16][17] The compact device had two cavities and three distributed Bragg reflectors (DBRs), and had gain layers in the one of the cavities. By contrast, in the other cavity, DFG of the two-color laser produced in the device was performed, where the generated electromagnetic waves then exhibited THz-wave properties.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain terahertz emission through DFG without external light sources, we have fabricated the structure by current injection from the viewpoint of practical device application. [20][21][22][23] The opposite signs of χ (2) (second-order nonlinear susceptibility) in the two cavity regions are necessary to realize a stronger THz-DFG of two modes. The sign of χ (2) can be inverted by the 180°rotation of the crystal around the appropriate axis.…”
Section: Introductionmentioning
confidence: 99%
“…In our most recent study, we demonstrated two-color lasing from a strongly coupled two-cavity system that contains InGaAs MQWs with two different well widths solely in the upper cavity layer. 32) The coupled cavity structure of that study was formed without using the wafer bonding method and the two-color lasing of the currentinjection device was observed under pulsed conditions at room temperature. In this study, we fablicated currentinjection surface-emitting devices using a wafer-bonded coupled cavity containing InGaAs MQWs and investigated their emission properties.…”
Section: Introductionmentioning
confidence: 99%